Enhancement of Light Output Power from LEDs Based on Monolayer Colloidal Crystal. Issue 9 (14th February 2014) - Geng, Chong; Wei, Tongbo; Wang, Xiaoqing; Shen, Dezhong; Hao, Zhibiao; Yan, Qingfeng
<x xml:space="preserve">Abstract</x> One of the major challenges for the application of GaN‐based light emitting diodes (LEDs) in solid‐state lighting lies in the low light output power (LOP). Embedding nanostructures in LEDs has attracted considerable interest because they may improve the LOP of GaN‐based LEDs efficiently. Recent advances in nanostructures derived from monolayer colloidal crystal (MCC) have made remarkable progress in enhancing the performance of GaN‐based LEDs. In this review, the current state of the art in this field is highlighted with an emphasis on the fabrication of ordered nanostructures using large‐area, high‐quality MCCs and their demonstrated applications in enhancement of LOP from GaN‐based LEDs. We describe the remarkable achievements that have improved the internal quantum efficiency, the light extraction efficiency, or both from LEDs by taking advantages of diverse functions that the nanostructures provided. Finally, a perspective on the future development of enhancement of LOP by using the nanostructures derived from MCC is presented.